Analisis Bibliometrik dengan Vosviewer terhadap Tingkat Kecemasan Wanita Menopouse di Google Scholar - Indarwati, Indarwati; Mursudarinah, Mursudarinah (Universitas Muhammadiyah Klaten, 2024)
Physical changes, health problems and psychology during menopause are the reasons for the high level of anxiety in women. Women who have negative perceptions will have high levels of anxiety about menopause. Many studies have been conducted on menopause, but it is not yet known what variables have been widely analyzed. Objectives, Researchers intend to 1) find out the development of research on anxiety in menopausal women, 2) map the development of research on anxiety in menopausal women. To answer these questions, the bibliometric analysis method uses Vosviewer on secondary data from previous research results. Meta data sources are taken from Google Scholar with the keywords: menopause, description, perception, anxiety. Publis or Perish is used to harvest and screen the desired variables for analysis. The years 2017 to 2023 were selected. 500 published articles of research results have an h index and have been cited, articles are selected from reputable international journals and internationally registered in the international home database. The results found that the development of research related to the topic of anxiety in menopausal women has not receded, but still exists. The complexity of the problems of menopausal women to experience anxiety is very diverse and affects the survival of women. With the presentation of the results of the descriptive analysis, it can be said that research related to menopausal anxiety will continue to increase over time, with various variables that appear in menopausal women. For further researchers, they can continue the study on the variables of the influence of menopausal women's anxiety on women's physical disorders.